(Invited) Xenes: A New Emerging Two-Dimensional Materials Platform for Nanoelectronics. (19th August 2016) - Molle, Alessandro
Abstract : The recent discoveries of silicene, germanene, and stanene, commonly denoted as Xenes (with X being Si, Ge, Sn), and their ligand-functionalized "Xane" derivatives, brings to the forefront an important class of two-dimensional (2D) elementary crystals. Similar to graphene, these materials are comprised of group IV atoms arranged in a honeycomb lattice, but with varying degrees of buckling that inherently stem from the interplay of sp2 and sp3 hybrid bonds. So far, Xenes were synthesized as epitaxially grown monolayers on substrates. An overview of the state-of-the-art on the Xenes-on-substrates will be here given. The silicene-on-silver will be taken as a representative example of the Xenes. Generally, two aspects qualify the epitaxy of Xenes on substrates, the emergence of a vertically buckled lattice and the strong interaction with the hosting substrate. The former fact may offer a potential to access to (and control of) the quantum spin Hall state in Xenes. This perspective is highly appealing as a new paradigm shift in nanoelectronics, and it will be briefly outlined. The latter fact is currently limiting an easy exploitation of Xene for functional applications and device integration. As a viable solution, the delamination of an encapsulated silicene monolayer will be presented as operative process for the fabrication of a silicene transistor that can be universally extended to other epitaxial Xenes.